Teaching academic writing through collaborative peer review: The undergraduate thesis in Psychology - Mariona Corcelles Seuba; Maribel Cano Ortiz; Gerardo Bañales Faz; Norma Alicia Vega (Universitat Politècnica de València, 2013)
Last years, numerous proposals have been designed to improve students' academic literacy at the university context but few have focused on teaching a specific genre such as the research article. Within the framework of the undergraduate thesis in Psychology, this study examines an intervention that aimed to improve the writing quality of this type of discourse. Such intervention combined collaborative peer review with the review of the teacher. We analyzed the type and number of suggestions made by peers and by the teacher and its acceptance or rejection to understand its impact on the final text quality. The sample involved 35 students and 8 teachers. A longitudinal design ex-post facto in a single group with repeated measures was used in which the dependent variable was the quality of the text and the independent variables were peer and teacher review. Results of the study showed that this methodology promoted the continuous revision of the text, which affected the quality of the final texts. Peers provided more suggestions than teachers and also had greater acceptance rate. However, these suggestions were mainly directed to the revision of the formal aspects while the teacher's suggestions referred, firstly, to aspects of coherence and cohesion, secondly, to formal aspects and finally, to involvement of the reader and author's position which were aspects that had a greater impact on the final texts quality.